Predicting Fork Visibility Performance on Programming Language Interoperability in Open Source Projects - Bee, Bee; bernardo, d. (International journal of advanced computer science & applications, 2018)
Despite a variety of programming languages adopted in open source (OS) projects, fork variation on some languages has been minimal and slow to be adopted, and there is little research as to why this is so. We therefore employed a K-nearest neighbours (KNN) technique to predict the fork visibility performance of a productive language from a pool of programming languages adopted in projects. In total, 38 showcase OS projects from 2012 to 2016 were downloaded from the GitHub website and categorized into different levels of programming language adoption clusters. Among 33 languages, JavaScript is one of the popular languages that adopted by community. It has been predicted the language chosen when fork visibility is high can increase project longevity as a highly visible language is likely to occur more often in projects with a significant number of interoperable programming languages and high language fork count. Conversely, a low fork language reduces longevity in projects with an insignificant number of interoperable programming languages and low fork count. Our results reveal the survival of a productive language is in response to high language visibility (large fork number) and high interoperability of multiple programming languages.